Faktor yang berhubungan dengan Kejadian Gizi Kurang pada anak Balita di Wilayah Kerja Puskesmas Waru Seram Bagian Timur. - Griennasty Siahaya; Zasendy Rehena (MOLUCCAS HEALTH JOURNAL, 2021)
The degree of public health can be seen from various factors which include indicators of life expectancy, mortality rate, number of visits and nutritional status of the community, especially in toddlers. Toddlers are the age group that most often suffers from malnutrition. Malnutrition or underweight is a toddler's failure to achieve the ideal weight, which can then affect the growth of height. This study aims to determine the factors associated with the incidence of malnutrition in children under five in the working area of the East Waru Seram Health Center. The type of research used is Cross Sectional with a sample of 157 toddlers in the working area of the Waru Health Center. Statistical test using chi-square test using univariate and bivariate analysis. The results of bivariate analysis showed that there was a relationship between exclusive breastfeeding (p = 0.044), consumption patterns (p = 0.44), and environmental sanitation (p = 0.035) with the incidence of malnutrition. The conclusion of this study is that there is a relationship between exclusive breastfeeding, food consumption patterns and environmental sanitation with the incidence of malnutrition in children under five in the working area of the East Waru Seram Health Center. Suggestions for mothers to offer exclusive breastfeeding and always follow posyandu activities.